Gibalna dejavnost in zdravstveno stanje zaposlenih v igralništvu - Mlinar, Suzana (Zdravstveno varstvo, 2009)
Objective: The aim of the study was to determine the differences in the experiences of stress as well as their state of health employees at the casinoemployees, by sports activity. Methods: The study included 251 employees(47.4 % men and 52.6 % women), aged 18 to 58 years. The sample of variables included the socio-demographic characteristics, stress, sports activity and state of health. Data analysis was done using basic statistical parameters and CHI2. Data was handled using SPSS 15.0 for Windows. Results: Regular sports activity was 51.4% participants. As well as they were estimating their state of health better than another the same aged (p = 0.017). Further, they were opining low frequencies of state of health (p = 0.034). Conclusion: Individuals who are regular sports activity evaluating their state of health better than those who are not regularly sports activity. Regular sports activity people are aware that the impacts of regular physical activity are part of the broad facet of a healthy lifestyle.
Keywords: gibalna dejavnost; igralništvo; stres; zdravstveno stanje